Forecasting Gross Domestic Product with Logistic Growth Model - Rahela Abdul Rahim; Noraziah Man; Fatinah Zainom (International Journal of Supply Chain Management, 2019)
Gross Domestic Product (GDP) is the sum of income for all goods and services acquired in a given time period. This study develops a model of GDP data for the state of Johor between 2005-2016 using the Logistic Growth model. Long-term GDP equilibrium values are predicted using non-linear equations and tested with different parameters. Forecasts of GDP in the near future are also presented using the appropriate parameters.